Survey on Good Hygiene Practices in Retail Meat Shops in Butwal Municipality, Nepal - Upadhayaya, M.; Ghimire, B. (Nepalese Veterinary Journal, 2018)
Present study was conducted to assess good hygiene practices in retail meat shops for safe and wholesome meat production as well to understand different roles performed by delegated institutions in ensuring quality meat production. A descriptive survey design was used to answer questions concerning the current status of meat hygiene and sanitation practices in the retail meat shops in Butwal municipality. Meat handlers from the meat shops were interviewed through a structured questionnaire. A total of 190 retail meat shops were analyzed randomly to assess their meat hygiene knowledge. It was found that 93.68% of the meat handlers had no regular health check up, 38.42% of the butchers didn’t use protective clothes, 95.26% of meat shops had no evisceration facility, 77.37% of meat shops disposed their waste materials in open space nearby, 96.84% lack lariage facilities and 99.47% did not follow ante-mortem and post-mortem inspection. There was a knowledge gap about Slaughterhouse and Meat Inspection Act 1999 within 96.32% of the meat handlers. The study recommends implementation of Slaughterhouse and Meat Inspection Act 1999 which has been approved in 1999 by the GoN to promote hygiene practices and animal welfare thereby improving the quality standard of meat shops and finally the quality of meat.